Naród" i kwestia żydowska w interpretacji Zygmunta Wasilewskiego w dobie zaborów III Rzeczypospolitej - Sobczak, Mieczysław (The "Nation" and The Jewishissue in the Interpretation of Zygmunt Wasilewski in The Times ff The Polish Annexation and in The 2nd Polish Republic, 2008)
The attitude of Zygmunt Wasilewski towards the Jewish issue was the result of his generał considerations about the national developments and the relations between them. In this context he was analyzing the power of the Polish nation in times of the Polish annexation and in the independent 2nd Polish Republic. He indicated that the power of the Polish nation ought to be strengthen. The basie thing was to strengthen the Polish relations. The Polish nation should differ from other nations having an unique national psychology and an uniąue spirit. The attitude towards national minorities should depend on the fact if the national minorities could be assimilated or not. In WasilewskPs point of view the Jewish nation could not be assimilated because of the different psyche. The Jewish people should be pushed away from the influence on the Pole's life.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 78-98